Damage reduction strategies against chemical accidents by using a mitigation barrier in Korean chemical risk management. (December 2018) - Lyu, Byeonggil; Lee, Kwanghee; Kim, Taejong; Cho, Hyungtae; Moon, Il
Highlights: Regulations and guidelines for risk management of chemical plant in Korea is introduced. Reducing damage to surrounding areas from a chemical-plant accident by building a mitigation barrier. Height of barrier is 20–33 m and length is 350 m to reduce vapor cloud dispersion. Computational fluid dynamics used to study barrier's mitigation effect. Abstract: After the hydrogen–fluoride release accident in 2012, the Korean society realized the importance of chemical safety and many plans have been proposed to improve it. After the big chemical accident, the "Chemical Control Act" was newly established. The law of the "Chemical Control Act" is the most representative measure for chemical safety. According to the law that came into force in 2015, all chemical dealing companies must conduct an off-site consequence analysis of their chemicals and develop a plan for risk management. To reduce off-site consequences from the chemical plant, an innovative risk-management plan was suggested by the Korean industry. A decision was made to build a 30 m high mitigation barrier outside the plant area to protect the public when a chemical release accident occurs. The construction is now under process, and two representative accident scenarios are developed for its simulation to confirm the effect of mitigation barrier. Each scenario follows guidelines of the "Chemical Control Act, " and simulation results show that the barrier helps reduce chemical concentration in the public area. This plan is expected to improve the anxiety of residents near the plant and will be a good example of risk management in the industry.